Why Follow the Leader? Collective Action, Credible Commitment and Conflict - Keefer, Philip (World Bank, Washington, DC, 2013)
Most analyses of conflict assume that conflicting groups act in a unitary fashion. This assumption is often violated: to reduce their risk of replacement, group leaders prevent both group members and soldiers from acting collectively, making it difficult for leaders to make credible commitments to them. Lifting the assumption that groups are unitary shifts the analysis of a wide range of conflict issues. The effects of income shocks and rents on conflict risk become contingent on collective action. Leader decisions regarding collective action explain the forcible recruitment of child soldiers and predation on civilians: leaders who prefer to limit military organization are more likely to pursue these tactics. Leader decisions regarding collective action also introduce an unexplored mechanism by which state capacity is created and a specific reason to regard state capacity as endogenous to conflict risk. This focus, finally, suggests that interventions to reduce conflict risk, such as safety net payments or service delivery, are likely to be most difficult to deliver precisely where leaders are most reluctant to allow collective action and where, therefore, conflict risk is highest.